2014
DOI: 10.1007/s10535-014-0419-4
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast elongation factor BcEF-Tu responds to turnip mosaic virus infection and heat stress in non-heading Chinese cabbage

Abstract: Eukaryotic elongation factor Tu has been implicated in responses to heat stress and viral infection. In this study, the turnip mosaic virus (TuMV)-response gene BcLRK01, which encodes a leucine-rich repeat receptor-like kinase, was probed using the cDNA library of TuMV-infected leaves of non-heading Chinese cabbage (Brassica campestris ssp. chinensis). The BcEF-Tu gene, which encodes chloroplast elongation factor Tu, was obtained and verified by a yeast two-hybrid system to interact with the BcLRK01 gene. TuMV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…A large number of recent studies, carried out using proteomic and transcriptomic approaches, have revealed how viral infection affects primarily the expression of CPRGs (Liu et al, 2014;Mochizuki et al, 2014a;Wu et al, 2013). RaLCB infection causes structural and functional damage to the chloroplast of Nicotiana benthamiana (Bhattacharyya et al, 2015) by selective suppression of gene expression; TMV flavum strain CP accumulates in and reduces the expression of tobacco chloroplast proteins, upsetting the efficiency of photosynthesis (Lehto et al, 2003); and TuMV infection suppresses the expression of the gene coding for chloroplast elongation factor Tu of Chinese cabbage (Peng et al, 2014) (Table 2). Virus-infected plants manifest striking mosaic symptoms (Channarayappa et al, 1992;Esau, 1933) associated with swollen chloroplasts, large amounts of starch and plastoglobulin accumulation and disintegrated grana stacks (Bhattacharyya et al, 2015;Otulak et al, 2015).…”
Section: Virus Infection Massively Changes the Structure And Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of recent studies, carried out using proteomic and transcriptomic approaches, have revealed how viral infection affects primarily the expression of CPRGs (Liu et al, 2014;Mochizuki et al, 2014a;Wu et al, 2013). RaLCB infection causes structural and functional damage to the chloroplast of Nicotiana benthamiana (Bhattacharyya et al, 2015) by selective suppression of gene expression; TMV flavum strain CP accumulates in and reduces the expression of tobacco chloroplast proteins, upsetting the efficiency of photosynthesis (Lehto et al, 2003); and TuMV infection suppresses the expression of the gene coding for chloroplast elongation factor Tu of Chinese cabbage (Peng et al, 2014) (Table 2). Virus-infected plants manifest striking mosaic symptoms (Channarayappa et al, 1992;Esau, 1933) associated with swollen chloroplasts, large amounts of starch and plastoglobulin accumulation and disintegrated grana stacks (Bhattacharyya et al, 2015;Otulak et al, 2015).…”
Section: Virus Infection Massively Changes the Structure And Functionmentioning
confidence: 99%
“…Physically, virus particles are often found to be associated with the chloroplasts of diseased hosts (Bhattacharyya et al, 2015;Lehto et al, 2003). Selective suppression of a set of genes (Bhattacharyya et al, 2015;Lehto et al, 2003) and/or targeted interaction with specific chloroplast proteins (Peng et al, 2014) can both produce massive changes in the organelle (Liu et al, 2014;Mochizuki and Ohki, 2011;Mochizuki et al, 2014b;P erez-Bueno et al, 2004;Pineda et al, 2010;Wu et al, 2013). For example, six distinct types of mosaic symptoms were manifested in different single point CP mutants of CMV-infected tobacco plants.…”
Section: Virus Infection Massively Changes the Structure And Functionmentioning
confidence: 99%
“…In our study, the abundance of chloroplastic EFTU protein increased in NaCl, and its expression further increased in SNP+NaCl treatment. Previous research has shown that EFTU plays a significant role in the high temperature tolerance of Brassica campestris plants (30). SNP-induced up-regulation of EFTU protein under salt stress conditions may repair the damaged photosynthetic proteins in chloroplasts by increasing protein biosynthesis under salt stress.…”
Section: Discussionmentioning
confidence: 95%